PASI (Psoriasis Area and Severity Index) in the evaluation of the clinical manifestations of psoriasis - A. A. Kubanov; A. E. Karamova; L. F. Znamenskaya; V. V. Chikin; V. V. Kondrashova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Psoriasis is one of the most prevalent chronic inflammatory skin diseases. The severity of its clinical manifestations can vary greatly. Objective assessment of psoriasis severity is required to select an adequate therapy. One of the simplest and most consistent methods used to determine psoriasis severity is to calculate the PASI (Psoriasis Area and Severity Index). This index is based on the doctor's determination of the sum of indices showing the intensity of the main symptoms of psoriasis: erythema, infiltration and peeling in view of the affected skin area. The PASI can also be used to assess the efficacy of treatment for psoriasis patients.